Interleaflet Coupling of Lipid Nanodomains – Insights From in vitro Systems - Sarmento, Maria J.; Hof, Martin; Šachl, Radek (Frontiers in Cell and Developmental Biology, 2020)
The plasma membrane is a complex system, consisting of two layers of lipids and proteins compartmentalized into small structures called nanodomains. Despite asymmetric composition of both leaflets, coupling between the layers is surprisingly strong. This can be evidenced, for example, by recent experimental studies performed on phospholipid giant unilamellar vesicles showing that nanodomains formed in the upper layer are perfectly registered with those in the lower leaflet. Similarly, microscopic phase separation in one leaflet can induce phase separation in the opposing leaflet that would otherwise be homogeneous. In this review, we summarize the current theoretical and experimental knowledge that led to the current view that domains are - irrespective of their size – commonly registered across the bilayer. Mechanisms inducing registration of nanodomains suggested by theory and calculations are discussed. Furthermore, domain coupling is evidenced by experimental studies based on the sparse number of methods that can resolve registered from independent nanodomains. Finally, implications that those findings using model membrane studies might have for cellular membranes are discussed.